2022
DOI: 10.3390/antibiotics11091268
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine and Inflammatory Cytokines in the Clinical Assessment of Infection in Venous Leg Ulcers

Abstract: Inflammation and biofilm-associated infection are common in chronic venous leg ulcers (VU), causing deep pain and delayed healing. Albeit important, clinical markers and laboratory parameters for identifying and monitoring persistent VU infections are limited. This study analyzed 101 patients with infected (IVU) and noninfected VUs (NVU). Clinical data were collected in both groups. The serum homocysteine (Hcys) and inflammatory cytokines from the wound fluid were measured. In addition, microbial identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Chronic wounds are disposed to bacterial infection, leading to serious complications. Managing wounds in the presence of infection is still challenging due to prolonged healing and frequent reoccurrence [7]. The recent development of new-generation sequencing targeting the species-specific small subunit ribosomal RNA (16S rRNA) gene and shotgun metagenomics allows the characterization of the skin and wound microbiota thanks to the ability to identify anaerobic microorganisms [54].…”
Section: Pathogen Colonization and Chronicity Of Woundsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chronic wounds are disposed to bacterial infection, leading to serious complications. Managing wounds in the presence of infection is still challenging due to prolonged healing and frequent reoccurrence [7]. The recent development of new-generation sequencing targeting the species-specific small subunit ribosomal RNA (16S rRNA) gene and shotgun metagenomics allows the characterization of the skin and wound microbiota thanks to the ability to identify anaerobic microorganisms [54].…”
Section: Pathogen Colonization and Chronicity Of Woundsmentioning
confidence: 99%
“…Chronic wounds of different etiologies showed that Staphylococcus and Pseudomonas were the most common genera, 63% and 25%, respectively [61]. A study on chronic venous leg showed that Gram-negative bacteria constituted 51.7%, mostly represented by Pseudomonas aeruginosa, followed by Escherichia coli, Serratia marcescens, Enterobacter cloacae, and Morganella morganii, while the Gram-positive bacteria constituted 48.3%, with Staphylococcus aureus as the dominant species [7]. Indeed, the colonization of the chronic wound is characterized by the presence of multiple microorganisms, initially by Gram-positive belonging to Staphylococcus genera, which do not elicit strong immune responses [62], and subsequently, by Gram-negative bacteria such as Pseudomonas spp., E. coli, Klebsiella pneumoniae, and Enterobacter spp., which become the predominant species in the microenvironment.…”
Section: Pathogen Colonization and Chronicity Of Woundsmentioning
confidence: 99%
See 3 more Smart Citations